Pengelolaan Jagung Menjadi Susu Bubuk Jagung Agar Meningkatkan Nilai Jual Jagung Pada Desa Bolo Kecamatan Madapangga Kabupaten Bima - Rimawan, Muhamad; Ismunandar, Ismunandar; Pratiwi, Aliah; Intisariharyanti, Intisariharyanti; Iftitah, Ita; Alwi, Alwi (Edumedia Solution, 2023)
Sweet Corn Milk is milk produced by processing sweet corn where because the sugar content of it has been used in it then the use of sugar will certainly be much less even if the bias is not used at all. Sweet Corn Milk is very beneficial for our metabolism for both children and adults and seniors. Compared to ordinary milk the content of vitamins and minerals is also not much different and has also had its own color of corn used which is a bit yellowish so it gives rise to an appetite to drink it. Corn milk is obtained by grinding corn seeds that have been boiled in water. The mill results are filtered to obtain filtrate which is then pasteurized and flavored to enhance the taste. The content of carbohydrate extracts in corn milk is influenced by corn varieties, the amount of water added, the length of time and storage conditions, the smoothness of the mill, and the heat treatment. The advantages of corn milk compared to cow's milk or soybeans are the raw materials are easy to come by at a not very high price. Corn does not contain lactate intolerance (which makes milk smell fishy). Corn milk contains more fiber, suitable for those who diet. Some corn benefits our health. A Rich Source of Caloric, Prevention of Bowel Cancer and Hemorrhoids, A Vitamin-Rich Source, Contains The Necessary Minerals, Antioxidant Properties of Corn, Protects the Heart, Prevents Anemia, Lowers Bad Cholesterol, Protection against Diabetes and Hypertension. If we process with a little food processing technique into corn milk then it will be worth more with different appearances and flavors that can be customized to the taste of consumers. So it is expected that with this activity mothers and people who participate in the activity can obtain knowledge and information on how to make corn milk. Corn milk can be consumed alone or sold to supplement the family’s income.